Laparoscopic Vascular Injury Simulation for Gynecology Residents. (October 2015) - Saad, Christina A.; Kim, David S.; Solnik, M. Jonathon; Wong, Melissa S.
Abstract : OBJECTIVE: To improve resident competence in managing laparoscopic vascular injuries using simulation. BACKGROUND: Although potentially catastrophic, luckily vascular injuries in gynecology are rare. Thus, opportunity to gain proficiency in management is rare. Thus, residents have limited exposure to this complication in vivo requiring the development of simulated experiences. METHODS: Residents participated in a simulated laparoscopic procedure. A mannequin containing basic vascular anatomy allowed for bleeding to occur. Residents participated in the simulation, underwent a debriefing, attended a lecture on the management of vascular injury, then repeated the simulation. Residents took a pretest, an immediate posttest, and a late posttest 2 weeks later. The tests contained survey questions, knowledge-based questions, and a free-text portion to simulate dictation. RESULTS: Twelve residents participated. Two (17%) had ever been involved in a vascular injury. Two (17%) had ever received prior instruction on management of vascular injury. The paired t test was used to analyze the data. Knowledge scores improved from 48% on the pretest to 88% on the early posttest ( P <.001) and 74% on the late posttest ( P =.002). Qualitative dictation scores improved from 11% on the pretest to 43% on the early posttest ( P =.005) and 30% on the late posttest ( P =.009). Resident confidence improved from 4% on the pretest to 42% on the early posttest ( P <.001) and 56% on the late posttest ( P <.001). One hundred percent felt the simulation was either quite helpful or extremely helpful. One hundred percent wanted it repeated annually. CONCLUSION: Our residents rarely see laparoscopic vascular injuries or learn about their management. This simulation showed a meaningful, statistically significant, and durable improvement in resident knowledge, confidence, and dictation quality. It was widely accepted by the residents and unanimously chosen to be part of the annual curriculum.